Cytotoxicity of methanol and aqueous Lignosus rhinoceros (Tiger Milk mushroom) extracts on HCT 116 human colorectal cancer cells and its mode of action / Suziana Zaila Hj Che Fauzi - Hj Che Fauzi, Suziana Zaila (2016)
Cancer is a very dangerous disease and fear by many. The available clinical treatment of cancer as chemotherapy, radiotherapy and surgery was expensive, toxic that cause severe effects and follow the concept of one drug - one target action. In this study, natural product which is Lignosus rhinocerus, commonly known as Tiger Milk mushroom, belongs to Polyporaceae family was used because of their less toxicity and cheaper than synthetic drugs. The mushroom is traditionally used in Malaysia for many beneficial claims such as cough, asthma, fever, chronic hepatitis and cancer. The biological activity of L. rhinocerus was investigated in terms of its cytotoxic effects, mode of cell death and antioxidant capacity. The antiproliferative activity of methanolic and aqueous PLEs was determined using MTT cell viability assay, where IC₅₀ value was used as a parameter for mode of cell death. MTT assay showed that both extracts significantly reduced the cell viability in a dose-dependent manner. Our results showed that methanol PLE of Lignosus rhinocerus sclerotia was found to exhibit antiproliferative activity against HCT 116 cells, with an IC₅₀ of 600 μg/mL and 1200 |μg/mL for aqueous PLE but not cytotoxic to normal human colon cell (CCD-I8-C0) and fibroblast Chinese hamster lung cell (V79-4). The IC₅₀values suggested that the solvent differences in pressurized liquid extraction greatly affected their antiproliferative activites. The Tiger Milk mushroom PLE arrested HCT 116 cells at G2/M phases with corresponding decreased in S-phase. The types of cell death were explored by flow cytometry using the Annexin V/FITC and propidium iodide and the dead end fluorometric TUNEL System. The mode of cell death induced by Lignosus rhinocerus PLEs was primarily apoptosis by extemalization of phosphatidylserine and DNA damage detected by 3'-OH DNA ends labelling. Additionally, weak antioxidant capacities were detected in both methanol and aqueous PLE of L. rhinocerus by the FRAP (Ferric Reducing Antioxidant Power) Assay. However, this extract did not increase the endogenous antioxidant capability when tested against HCT 116 cells. Preliminary phytochemical screening revealed that both methanol and aqueous pressurized liquid extraction of L. rhinoceros contained alkaloids. The above data suggested that pressurized liquid extraction (PLE) extract of the sclerotia of L. rhinocerus possesses cytotoxicity to human colorectal cancer cells but were non-toxic to the corresponding normal cells. The results suggest that Tiger Milk mushroom stimulates apoptosis through G2/M cell cycle arrest.